INTERACTION STUDIES OF TWEEN-40 WITH SOME ACIDIC SPECIES AT 20 0C - Mahmood, Farzana; Arif, Muhammad; Ahmed, Ayyaz; Niazi, Shahida B. (Journal of Research (Science), 2000)
Interactions of tween-40 (polyoxyethylene-20-sorbitain monopalmitate) with acetic acid, chloroacetic acid, o-, m-, p-nitrophenols and picric acid have been described at 20oC using conductivity method. The studies are performed at cmc with an emphasis on pre- and post micellar regions. Data thus obtained is used to manipulate the interactions. Binding constants of the species have been computed using Satake equation, standard free energy changes are also obtained to further justify the results.